Science-fiction et traduction en Chine continentale : d’outils pour le progrès à outils de soft power - Loïc Aloisio (ReS Futurae)
Drawing first on the polysystem theory and then on Lefevere’s notion of patronage, this article sets out to highlight the role played by translation, firstly in the popularisation of the genre in Mainland China and in its evolution and definition, in order to explore how an “imported” genre has been continually reworked and brought to the fore at each period ; and secondly as a tool for “re-exporting” the genre, which is now fairly well assimilated, from the People’s Republic of China to other countries, with the Chinese government promoting science fiction as a soft power tool designed to tell the country’s “bright future”.